Pengaruh Green Accounting, Corporate Social Responsibility Disclosure dan Earnings Quality Terhadap Firm Value Melalui Profitibility sebagai Variabel Intervening - Widya Permata Sari; Nera Marinda Machdar (Jurnal Kajian dan Penelitian Umum, 2023)
This research aims to examine the influence of green accounting, disclosure of corporate social responsibility, and earnings quality. The population in this research is all manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2022 period. The sampling technique used was the purposive sampling method. The analysis method used is Multiple Linear Regression. The research results show that green accounting does not have a positive effect on Firm value; disclosure of corporate social responsibility has a positive effect on Firm value; earnings quality has a negative effect on Firm value; green accounting has a positive effect on profitability; disclosure of corporate social responsibility has a positive effect on profitability; earnings quality has a positive influence on profitability; green accounting has a positive effect on Firm value with profitability as an intervening variable; disclosure of corporate social responsibility has a positive effect on Firm value with profitability as an intervening variable; earnings quality has a positive effect on Firm value with profitability as an intervening variable; and Profitability has a positive effect on Firm value.